PERTUMBUHAN EKONOMI DAN KEGIATAN EKONOMI ANGKATAN KERJA DI PROVINSI BALI - Nyoman Dayuh Rimbawan (PIRAMIDA, 2010)
Economic growth is one of macroeconomics indicators. In every developmentprocess, economic growth always becomes an important target, even though it is not a goodindicator to determine development success. A relatively high economic growth is notidentical with increase of welfare. Therefore other indicators are needed, such as povertyindex, unemployment index, income distribution, and so on.During the period of 2005-2009 Bali economic growth fluctuated with trend todecrease. It grew at of 5.61 percent in average, while nationally reached above 6.00 percent.Job opportunities increased, but this was due to half-employment (work less than 35hours/week) and unpaid employment.Poverty index also decreased, but it was not the case in rural areas. This might becaused by a huge worker productivity gap among job fields. For instance, productivity perworker in agriculture ranks eight out of nine job fields.All facts mentioned above show that Bali economics growth has not been optimum, inwhich 50 percent was contributed by household consumption and less than 10 percent byinvestment. Optimum growth will be achieved if most activities are pushed by investment.